Analisis Potensi Fraud Laporan Keuangan Perbankan: Studi Empiris Menggunakan F-Score - Kresencia Yolanda Andreas; Nazwa Hana Faradila; Monica Chandra; Daniel Satrio Prakoso; Yanuar Ramadhan (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to analyse indications of financial statement fraud in the banking sector classified as Core Capital Group (KBMI) 3 and 4 listed on the Indonesia Stock Exchange (IDX) for the period 2024. This study employs a quantitative approach using the Dechow F-Score as a tool to detect indications of fraud. The data used are sourced from the public financial statements of banking companies. The results of the study indicate that nearly all banks in KBMI 3 and 4 show no indications of financial statement fraud. This study contributes to the development of literature by applying the Dechow F-Score to the Indonesian banking sector. The main limitation of this study lies in the sample size of 13 companies. Nevertheless, the results of this study provide important implications for being more vigilant against indications of fraud.